2002
DOI: 10.1093/jac/dkf178
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and ocular penetration of grepafloxacin in albino and pigmented rabbits

Abstract: The pharmacokinetics of grepafloxacin were determined in albino and pigmented rabbits following a single 10 mg/kg intravenous administration. The penetration of grepafloxacin into various ocular tissues was also determined after continuous intravenous infusion in both types of animal. Grepafloxacin showed a bicompartmental model of distribution in both pigmented and albino rabbits with significant differences in the pharmacokinetics between the two types of animal. After continuous intravenous infusion, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…The difference in the strain (respectively, Dutch belted versus New Zealand) and weight (respectively, 2.2 to 2.5 kg versus 3.0 to 4.0 kg) of the rabbits used could partially explain the difference observed, because the vitreous volume of the tested rabbits could vary significantly. Ocular pigmentation could also play a role, since the affinity of daptomycin to melatonin could affect the intraocular pharmacokinetics of this antibiotic, as it has already been implicated in some studies comparing intraocular penetration of systemic antibiotics in albino and pigmented rabbits (15,19). The difference in the tested bacterial species (S. aureus versus S. epidermidis) could modify the bacterial toxin profiling and could explain the differences in strain virulence and histopathologic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the strain (respectively, Dutch belted versus New Zealand) and weight (respectively, 2.2 to 2.5 kg versus 3.0 to 4.0 kg) of the rabbits used could partially explain the difference observed, because the vitreous volume of the tested rabbits could vary significantly. Ocular pigmentation could also play a role, since the affinity of daptomycin to melatonin could affect the intraocular pharmacokinetics of this antibiotic, as it has already been implicated in some studies comparing intraocular penetration of systemic antibiotics in albino and pigmented rabbits (15,19). The difference in the tested bacterial species (S. aureus versus S. epidermidis) could modify the bacterial toxin profiling and could explain the differences in strain virulence and histopathologic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones are a group of synthetic antibiotics chemically related to nalidixic acid. These compounds have been developed for the treatment of a variety of microbial infections in both animal and human medicine (Abadia et al, 1995;Garcia et al, 1999a;McKellar et al, 1999;Bregante et al, 1999;Perez et al, 2002). These agents work by inhibiting the action of DNA gyrase, interfering with the supercoiling of antibacterial chromosomal material (Cornett and Wentland, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In common with systemic grepafl oxacin administration, we have found that intravitreal grepafl oxacin administration is associated with the highest concentrations being found in the chorioretina and iris of pigmented rabbits [8,35] . However, our results on the grepafl oxacin concentrations in the sclera have to be viewed with some caution, because this tissue is very diffi cult to separate from the chorioretina.…”
Section: Discussionmentioning
confidence: 84%
“…This antimicrobial agent can be considered a member of the third-generation fl uoroquinolone family and can be studied as a model of penetration and activity for this group of antimicrobial agents [8] . In an earlier paper [8] , we studied the pharmacokinetics and ocular penetration of grepafl oxacin in albino and pigmented rabbits following intravenous administration of grepafl oxacin, with good penetration into several ocular tissues.…”
mentioning
confidence: 99%